Fiber ICAN laser with exawatt-picosecond pulses for fusion without nuclear radiation problems. (March 2014) - Hora, H.; Lalousis, P.; Moustaizis, S.
Abstract: One of the numerous applications of the ICAN laser using the advantage of fiber optics with chirped pulse amplification (CPA), is the scheme of side-on initiation of a nuclear fusion flame in solid density fuel with laser pulses of shorter than picosecond (ps) duration and power in the petawatt (PW) and higher range. The ICAN Fiber optics has special advantages with the potential that >900 PW spherical laser pulses may ignite the proton reaction with 11 B (HB11) without the problem of dangerous radioactive radiation. Though secondary reactions can be estimated very roughly, the feasibility of a power station with the necessary energy gains can be concluded.